Vive la diversité! High Reliability Organisation (HRO) and Resilience Engineering (RE). (August 2019) - Le Coze, Jean Christophe
Highlights: HRO and RE are two influential research traditions in the field of safety today. They originate from different programs thirty years ago. A short history of the two schools is introduced as a basis for discussion. The two schools are then compared and their specific intellectual orientation highlighted. Abstract: High Reliability Organisation (HRO) and Resilience Engineering (RE) are two research traditions which have attracted a wide and diverse readership in the past decade. Both have reached the status of central contributions to the field of safety while sharing a similar orientation. This is not without creating tensions or questions, as expressed in the call of this special issue. The contention of this article is that these two schools introduce ways of approaching safety which need to be reflected upon in order to avoid simplifications and hasty judgments about their relative strength, weaknesses or degree of overlapping. HRO has gained strength and legitimacy from (1) studying ethnographically, with an organisational angle, high-risk systems, (2) debating about principles producing organisation reliability in face of high complexity and (3) conceptualising some of these principles into a successful generic model of "collective mindfulness", with both practical and theoretical success. RE has gained strength and legitimacy from (1) harnessing then deconstructing, empirically and theoretically, the notion of 'human error', (2) argued for a system (and complexity) view and discourse about safety/accidents, (3) and supported this view with the help of (graphical) actionable models and methods (i.e. the engineering orientation). In order to show this, one has to go beyond the past 10 years of RE to include a longer time frame going back to the 80 s to the early days of Cognitive Engineering (CE). The approach that is followed here includes therefore a strong historical orientation as a way to better understand the present situation, profile each school, promote complementarities while maintaining nuances.